Vitamin D and Acute Kidney Injury: A Two-Way Causality Relation and a Predictive, Prognostic, and Therapeutic Role of Vitamin D - Graidis, Spyridon; Papavramidis, Theodosios S.; Papaioannou, Maria (Frontiers in Nutrition, 2021)
Background: Acute kidney injury (AKI) constitutes a multi-factorial caused condition, which significantly affects the kidney function and can lead to elevated risk of morbidity and mortality. Given the rising scientific evidence regarding vitamin D’s (VitD) multisystemic role the connection between AKI and VitD is currently studied and the complex relation between them has started to unravel. Methods: A systematic review had been conducted, to identify the pathogenetic relation of VitD and AKI and the potential role of VitD as biomarker and therapeutic-renoprotective factor. Results: From 674 articles identified 74 articles fulfilled the inclusion criteria. Based on these articles, it has been found that not only VitD disorders (VitD-deficiency or toxicity) can cause AKI, but, also, AKI can lead to great disruption in the metabolism of VitD. Moreover, it has been found that VitD serves as a novel biomarker for prediction of the risk of developing AKI and for the prognosis of AKI’s severity. Finally, animal models showed that VitD can both ameliorate AKI and prevents its onset, suggesting its renoprotective effect. Conclusion: There is a complex two-way pathogenetic relation between VitD disorders and AKI, while, concomitantly, VitD serves as a potential novel predictive-prognostic biomarker and a treatment agent in AKI therapy.